Does Job Satisfaction Affect Work Environment, Leadership, and Organizational Culture with Motivation as a Mediator ? - Rahmad Hartono (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The research report analyses Job Satisfaction influenced by Work Environment, Leadership, and Organizational Culture, through Motivation. Data collection was carried out in July 2022 for all 136 employees. Thirty respondents were assigned to test the validity and reliability, and the remaining 96 were for calculating multiple linear regression. Model feasibility test for two substructures, t-test for partial testing, and Sobel test to determine indirect effects. The analysis results conclude that the work environment variable affects the motivation variable, but there is no effect on employee satisfaction. Leadership Variables do not influence Motivation and Job Satisfaction. Organizational Culture influences variable Job Satisfaction, but Organizational Culture does not affect Motivation. Motivational Variables influence Job Satisfaction. In an indirect relationship, the three variables can directly affect the endogenous variables.